50 Successful improvement in the quality of cleaning and disinfection at a specialized tertiary care hospital in riyadh, saudi arabia. (25th October 2019) - Yassine, Kassem Abou; Alshamrani, Majid; Badawi, Ayham Al; Alrasheed, Nada; Alhawtan, Mustafa; Alaidan, Basma; Bakheet, Yahya Al; Alameer, Kholoud; Caswell, Angela; Malki, Majid; El-Saed, Aiman
Abstract : Background: Environmental cleaning is critical for reducing the burden of healthcare-associated infections and multidrug-resistant organisms. The objective of the current study was to improve the quality of cleaning and disinfection done by housekeepers. Methods: An interventional study was done between October 2018 and February 2019. The intervention included training of 130 housekeeping staff; redefining cleaning and disinfection responsibilities between housekeeping and nursing; adding a checklist for surfaces to be cleaned or disinfected; and emphasizing the inspector's auditing role. The intervention engaged relevant staff partners from infection control, housekeeping, nursing, and environmental services. The study outcome was the frequency of effective cleaning done by housekeepers. It was assessed by comparing the photos taken from specified room sites (pre-prepared by fluorescent gel) using black light before and after cleaning. Six highly touched areas in patient rooms were chosen. The study was divided into three phases: pre-intervention assessment (October 2018), intervention (November 2018 through January 2019), and post-intervention reassessment (February 2019). Results: A total of 27 rooms with 162 opportunities were assessed during the pre-intervention phase. The findings showed that only 39 (24.1%) of the 162 opportunities were effectively cleaned. The frequencies of effective cleaning in different sites were: light switches 11.1%, door knobs 25.9%, water faucets 37%, telephones 25.9%, bed rails 14.8%, and patient tables 29.6%. A total of 33 rooms with 198 opportunities were assessed during the post-intervention phase. The findings showed that 116 (58.6%) of the 198 opportunities were effectively cleaned. The frequencies of effective cleaning in different areas were: light switches 42.4%, door knobs 84.8%, water faucets 75.7%, telephones 60.6%, bed rails 54.5%, and patient tables 63.6%. The overall improvement in effective cleaning in different sites was 34.5% (p<0.001), being highest for door knobs (58.9%, p<0.001) and lowest for light switches (31.3%, p=0.014). Conclusion: A multidisciplinary intervention including training and auditing of housekeepers was successful in significantly improving cleaning and disinfection at different sites in the patients' rooms. Frequent assessment and feedback may need to be continued until reaching an optimal level. Further studies are needed to evaluate the impact of improved cleaning on infection rates.